Implications of the COVID-19 Pandemic on Children and Adolescents: Cognitive and Emotional Representations - Alexandra Maftei; Ioan-Alex Merlici; Iulia-Cristina Roca (MDPI AG, 2022)
The present research investigated children and adolescents' explicit and spontaneous representation of the COVID-19 pandemic and their related emotions, cognitions, and coping strategies. We explored the self-reported protective factors and coping mechanisms, in addition to similar attributional emotional experiences, i.e., the ways participants evaluated others' pandemic experiences. Our sample consisted of 155 children and adolescents aged 10 to 13 (M = 10.70, SD = 0.85, 56.1% females). We designed a 12-item survey and analyzed our data using both qualitative and quantitative methods. Our findings suggested that most children and adolescents associated masks with the thought of the novel coronavirus, and the most frequently associated emotion was sadness (45.2%), followed by fear (17.4%). Generally, participants reported a medium level of perceived adverse effects of the pandemic, mainly because their regular physical school classes moved to the online setting. We also found a significant association between children's self-reported levels of harmful effects of the pandemic and perceived adverse effects on their families. Most participants expressed their dissatisfaction concerning online school classes, primarily due to poor online interaction. In our sample, the children and adolescents reported positive thoughts and family relationships as their primary coping mechanisms during the pandemic, suggesting similar perceived coping mechanisms in the others around them. Finally, more than half of the participants considered that the COVID-19 pandemic had no positive effects, while 40% considered the increased time spent with their families the primary positive consequences following the COVID-19 health crisis. Results are discussed regarding their implications concerning healthcare, social, and educational policies.